Iron overload alters the energy metabolism in patients with myelodysplastic syndromes: results from the multicenter FISM BIOFER study - Cilloni, Daniela; Ravera, Silvia; Calabrese, Chiara; Gaidano, Valentina; Niscola, Pasquale; Balleari, Enrico; Gallo, Daniela; Petiti, Jessica; Signorino, Elisabetta; Rosso, Valentina; Panuzzo, Cristina; Sabatini, Federica; et al. (Scientific reports, 2020)
Myelodysplastic syndromes (MDS) are hematological malignancies characterized by ineffective hematopoiesis and increased apoptosis in the bone marrow, which cause peripheral cytopenia. Mitochondria are key regulators of apoptosis and a site of iron accumulation that favors reactive oxygen species (ROS) production with detrimental effects on cell survival. Although the energy metabolism could represent an attractive therapeutic target, it was poorly investigated in MDS. The purpose of the study was to analyze how the presence of myelodysplastic hematopoiesis, iron overload and chelation impact on mitochondrial metabolism. We compared energy balance, OxPhos activity and efficiency, lactic dehydrogenase activity and lipid peroxidation in mononuclear cells (MNCs), isolated from 38 MDS patients and 79 healthy controls. Our data show that ATP/AMP ratio is reduced during aging and even more in MDS due to a decreased OxPhos activity associated with an increment of lipid peroxidation. Moreover, the lactate fermentation enhancement was observed in MDS and elderly subjects, probably as an attempt to restore the energy balance. The biochemical alterations of MNCs from MDS patients have been partially restored by the in vitro iron chelation, while only slight effects were observed in the age-matched control samples. By contrast, the addition of iron chelators on MNCs from young healthy subjects determined a decrement in the OxPhos efficiency and an increment of lactate fermentation and lipid peroxidation. In summary, MDS-MNCs display an altered energy metabolism associated with increased oxidative stress, due to iron accumulation. This condition could be partially restored by iron chelation.